UNDERSTANDING THE CONCEPT OF ALGEBRAIC FORM USING APOS THEORY IN TERMS OF PERSONALITY TYPE - Sakdiyah, Halimatus; Manoy, Janet Trineke (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2023)
This research is based on descriptive research with a qualitative approach. The purpose of this study is to describe the understanding of the concept of algebraic form of junior high school students using APOS (Action, Process, Object, and Scheme) theory in terms of introverted and extroverted personality types. The instruments in this study are researchers (key instruments), personality type questionnaires, concept understanding tests and interviews (supporting instruments). Data collection techniques in this study using questionnaire, test and interview methods. The subjects in this study were one female student with introverted personality and one female student with extroverted personality. The results showed that the understanding of the concept of algebraic forms of introverted students based on APOS theory is at the action, process, object and scheme stages related to the concept of arithmetic operations of algebraic forms and is at the action stage related to the concept of solving contextual problems related to algebraic forms. While the understanding of the concept of algebraic form of extroverted students based on APOS theory is only at the action stage related to the concept of arithmetic operation of algebraic form and the concept of solving contextual problems related to algebraic form. Researchers hope that this research can be used as a consideration for teachers to pay more attention to the type of personality possessed by students, so that concepts can stick and reduce the occurrence of misunderstanding of concepts